The Emerging Role of Quercetin in the Treatment of Chronic Pain - Liu, Cheng; Liu, Dai-Qiang; Tian, Yu-Ke; Mei, Wei; Tian, Xue-Bi; Xu, Ai-Jun; Zhou, Ya-Qun (Current Neuropharmacology, 2022)
Despite much research efforts being devoted to designing alternative pharmacological interventions, chronic pain remains to be an unresolved clinical problem. Quercetin, a compound that belongs to the flavonoids family, is abundantly found in fruits and vegetables. Emerging evidence indicates that quercetin possesses anti-nociceptive effects in different rodent models of chronic pain, including inflammatory pain, neuropathic pain and cancer pain. In this review, we summarize the mechanisms underlying the analgesic effect of quercetin in preclinical studies. These studies showed that quercetin exerts potent analgesic effects against chronic pain via suppressing neuroinflammation and oxidative stress as well as modulation of synaptic plasticity, GABAergic system, and opioidergic system. Considering that the safety of quercetin is well established, it has great potential for clinical use in pain treatment.
Keywords: GABAergic system